1992
DOI: 10.1523/jneurosci.12-01-00153.1992
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in the barrel cortex of the adult mouse: effects of chronic stimulation upon deoxyglucose uptake in the behaving animal

Abstract: We investigated experience-dependent regulation of neuronal activity in the whisker-to-barrel pathway of the adult mouse using the autoradiographic deoxyglucose (DG) method. Animals were placed in the Lausanne whisker stimulator, and three of their whisker follicles were passively stimulated for a period of 1, 2, or 4 d. After this period, mice received a dose of DG and were placed in a cage containing a pile of wooden sticks. Mice that underwent the same procedure except the passive stimulation served as cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 23 publications
6
44
2
Order By: Relevance
“…In addition, we show that the depression of PW-evoked response is restricted to the "stimulated" barrel because responses in adjacent "nonstimulated" barrels C1 and D2 to their corresponding PW are not altered. These observations correlate well with the similarly localized decrease in deoxyglucose uptake described by Welker et al (1992). The depression of neuronal firing may be attributable to homeostatic downregulations of the cortical network to stabilize its own level of activity in response to a period of chronic increase in sensory drive.…”
Section: Attenuation Of Responses To the Pw In Layer IV Of The "Stim-supporting
confidence: 83%
See 2 more Smart Citations
“…In addition, we show that the depression of PW-evoked response is restricted to the "stimulated" barrel because responses in adjacent "nonstimulated" barrels C1 and D2 to their corresponding PW are not altered. These observations correlate well with the similarly localized decrease in deoxyglucose uptake described by Welker et al (1992). The depression of neuronal firing may be attributable to homeostatic downregulations of the cortical network to stabilize its own level of activity in response to a period of chronic increase in sensory drive.…”
Section: Attenuation Of Responses To the Pw In Layer IV Of The "Stim-supporting
confidence: 83%
“…Layer IV is the cortical entry of peripheral signals. In rodents, each barrel processes primarily sensory signals ascending from the corresponding whisker (Armstrong-James and Fox 1987;Simons 1978;Welker et al 1992), reflecting the segregation of TC-axonal branches from individual barreloids within the corresponding barrels (Arnold et al 2001;Bernardo and Woolsey 1987;Frost and Caviness 1980;Jensen and Killackey 1987;Killackey 1973). In mice and rats barrels contain glutamatergic neurons, mainly spiny stellate cells, and GABAergic inhibitory aspiny neurons (Harris and Woolsey 1983;Porter et al 2001;White 1978;White and Rock 1980).…”
Section: Attenuation Of Responses To the Pw In Layer IV Of The "Stim-mentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation per se is inadequate. When appropriate conditions of behavioral context are not met, no change, or even negative changes, may be the result (Welker et al, 1992;Polley, 2004). These findings substantially differ from the changes produced by behaviorally relevant stimulation versus deprivation in our study (See Figure 3).…”
Section: Directional Bias Of the Overlapping Areascontrasting
confidence: 82%
“…For example, Polley et al (1999) showed that the cortical area activated by whisker deflection actually shrinks after exposure to a sensoryrich environment in which animals are encouraged to use the whiskers. Second, passive whisker overstimulation of a single whisker leads to reduced 2-deoxyglucose uptake in the corresponding barrel columns (Welker et al, 1992).…”
Section: Behavioral Overuse Versus Callosal Influencesmentioning
confidence: 98%